KONFLIK AGRARIA YANG TAK PERNAH REDA - Zakie, Mukmin (Faculty of Law, University of Muhammadiyah Malang, 2016)
The ideal goal to be achieved by this country when it declared Law Number 5 of 1960 on the Basic Regulation of Agrarian is the prosperity of society, especially farmers and there is no more conflict. Conflicts before the law is one of them for their legal dualism governing agrarian question. Unification law which regulates the keagrarian expected to answer and give a solution to the conflict over the years. It turns out that the opposite is true, more and more regulations issued with respect to agrarian, it further adds new problems. Changes in the pattern and kareteristik conflict evolves with people's lives, mindset and outlook changed to agrarian particularly land, requires also look for a pattern resolution of the conflict. This paper attempts to it.